Niacin Increases Atherogenic Proteins in High-Density Lipoprotein of Statin-Treated Subjects. Issue 8 (17th June 2021) - Ronsein, Graziella E.; Vaisar, Tomas; Davidson, W. Sean; Bornfeldt, Karin E.; Probstfield, Jeffrey L.; O'Brien, Kevin D.; Zhao, Xue-Qiao; Heinecke, Jay W.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Niacin therapy fails to reduce cardiovascular events in statin-treated subjects even though it increases plasma HDL-C (HDL [high-density lipoprotein] cholesterol) and decreases LDL-C (LDL [low-density lipoprotein] cholesterol) and triglyceride levels. To investigate potential mechanisms for this lack of cardioprotection, we quantified the HDL proteome of subjects in 2 niacin clinical trials: the CPC study (Carotid Plaque Composition) and the HDL Proteomics substudy of the AIM-HIGH trial (Atherothrombosis Intervention in Metabolic Syndrome with Low HDL/High Triglycerides). Approach and Results: Using targeted proteomics, we quantified levels of 31 HDL proteins from 124 CPC subjects and 120 AIM-HIGH subjects. The samples were obtained at baseline and after 1 year of statin monotherapy or niacin-statin combination therapy. Compared with statin monotherapy, niacin-statin combination therapy did not reduce HDL-associated apolipoproteins APOC1, APOC2, APOC3, and APOC4, despite significantly lowering triglycerides. In contrast, niacin markedly elevated HDL-associated PLTP (phospholipid transfer protein), CLU (clusterin), and HP/HPR (haptoglobin/haptoglobin-related proteins; P ≤0.0001 for each) in both the CPC and AIM-HIGH cohorts. Conclusions: The addition of niacin to statin therapy resulted in elevated levels of multiple HDL proteins linked to increased atherosclerotic risk, which might have compromised the cardioprotective effects associated with higher HDL-C levels and lower levels of LDL-C and triglycerides. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT00715273; NCT00880178; NCT00120289.